The Establishment of Tax on Land and Building Rights (BPHTB) Payment Arrangement in Notarial Sale and Purchase Agreement Deed - Wahyuni, Fitri; Yusdiansyah, Efik; Sundary, Rini Irianti (JOM, 2024)
The transfer of land rights in Indonesia is governed by various positive laws currently in force, including Government Regulation Number 35 of 2023 (PP 35/2023) concerning General Provisions for Regional Taxes and Regional Levies. PP 35/2023 regulates the establishment of the Tax on Land and Building Rights (BPHTB), which is also imposed on the Sale and Purchase Agreement (PPJB) made by a notary. Specifically, the regulation addresses PPJBs that have been fully paid. However, this provision is not entirely consistent with the existing regulation requiring the payment of BPHTB for the Sale and Purchase Deed (AJB) executed by the Land Deed Making Officer (PPAT). This payment is a fundamental requirement for changing the name on the land and building title certificate, as stipulated by the National Land Agency. This study employs a normative legal research method, focusing on library materials or secondary data. Utilizing a qualitative approach, the research analyzes legal norms in statutory regulations. The findings indicate that PP 35/2023 still lacks a clear legal basis for recognizing a notary's PPJB as a condition for changing the name on the land certificate by the buyer.